A methodology to improve third sector investment strategies: the development and application of a Western Cape based financial resource allocation decision making model - Smit, Andre de Villiers (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DPhill (Social Work))—University of Stellenbosch, 2005.